Design of a Web-Based Vehicle Asset Information System at The Islamic Shariah Office in Banda Aceh City - Rafiqah, Nurul; Wali, Muhammad; Idwan, Harry (International Journal Software Engineering and Computer Science (IJSECS), 2023)
This study describes the design of a web-based vehicle information system for Islamic Shariah services in Banda Aceh City. An issue under discussion is the use of computers in the design of vehicle asset information systems. The purpose of this study is to examine the use of vehicle asset information systems. Data collection was conducted through literature and field surveys by interviews and direct observation of the objects in question. Extreme programming techniques are used in system development. The following can be concluded from the created application program: 1) Vehicle Asset Information System of Islamic Shariah Service can quickly and efficiently view the vehicle asset data system according to existing data, so you can get timely vehicle asset data reports. 2) Implementation of asset vehicle information system in Islamic Shariah office will make data processing faster, more accurate and more efficient. 3) Applying asset vehicle information system in Islamic Shariah office facilitates data retrieval and greatly reduces human and financial resources.